Variations of arbuscular mycorrhizal fungi following succession stages in a tropical lowland rainforest ecosystem of South China - Yang, Huai; Mai, Siwei; Liu, Wenjie; Fu, Jialin; Yang, Qiu; Zhang, Bin; Huang, Biao (Frontiers in Ecology and Evolution, 2023)
The main role of arbuscular mycorrhizal fungi (AMF) is to provide nitrogen and phosphorus for plants, which plays a major role in forest succession and is an important microbial community. The herbs and shrubs in Ganshiling can’t be successful for a long time. After 40-year recovery, the forest morphology of the secondary forest is basically the same as that of the 60-year recovery, but whether the microorganisms have recovered to the level of the secondary forest of 60-year? The understanding of the interaction between soil AMF and succession in tropical rainforest area is still limited. Therefore, the present study was conducted to investigate changes in AMF along forest succession and explore the impacts of the physical and chemical properties of soil. we conducted a second tropical lowland rainforest ecosystem of Nature Reserve of Ganshiling at southern Hainan Island, in grassland, shrubland, 40-year-old and 70-year-old secondary forest. The results show that: (1) the succession stage showed various effects along AMF communities. (2) after 40-year recovery, the alpha-diversity indices of AMF recovered to the level of 60-year secondary forest, whereas species of AMF (OTUs) did not recover to the level of 60-year secondary forest, the similarity of soil AMF communities only recovered to 25.3%. (3) Species richness of common species, rare species and all species of AMF showed significantly positive correlation with soil nitrogen. (4) Species richness, Shannon’s diversity index, Simpson’s diversity index and pielou’s evenness index of rare species of AMF exhibited significantly negative correlation with carbon nitrogen ratio. (5) The OTU10; OTU6, OTU9 and OTU141; OTU3 and OTU38; and OTU2, OTU15, OTU23 and OTU197 were significantly unique AMF for grassland, shrub, secondary forest of 40a and 60a, respectively. (6) The phylogenetic tree and heatmap of AMF showed that the distribution of OTUs at grassland and shrub were contrast to that at secondary forest of 40a and 60a. The successional trajectories of vegetation recovery after deforestation are likely limited by AMF species availability.